Frontiers in Biophotonics for Translational Medicine In the Celebration of Year of Light (2015) - Olivo, Malini; Dinish, U. S.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
The present book provides recent developments in various in vivo imaging and sensing techniques such as photo acoustics (PA) imaging and microscopy, ultrasound-PA combined modalities, optical coherence tomography (OCT) and micro OCT, Raman and surface enhanced Raman scattering (SERS), Fluorescence lifetime imaging (FLI) techniques and nanoparticle enabled endoscopy etc. There is also a contributing chapter from leading medical instrumentation company on their view of optical imaging techniques in clinical laparoscopic surgery. The UN proclaimed 2015 as the International Year of Light and Light-based Technologies, emphasizing achievements in the optical sciences and their importance to human beings. In this context, this book focusses on the recent advances in biophotonics techniques primarily focused towards translational medicine contributed by thought leaders who have made cutting edge developments in various photonics techniques.
Fluorescence Lifetime Spectroscopy and Imaging Techniques in Medical Applications -- Translational Photoacoustic Microscopy -- Advances in Optoacoustic Imaging: From Benchside to Clinic -- Raman Spectroscopy Techniques: Developments and Applications in Translational Medicine -- Deep Tissue Hemodynamic Monitoring Using Diffuse Optical Probes -- High Resolution Optical Coherence Tomography for Bio-imaging -- Handheld Probe-based Dual Mode Ultrasound/Photoacoustics for Biomedical Imaging -- Plasmonic Exosome Biosensors for Medical Diagnostics -- Nanoparticle-enabled Endoscopy: Extending the Frontiers of Diagnosis and Treatment -- Monitoring Free Gas In-situ for Medical Diagnostics Using Laser Spectroscopic Techniques -- Next Frontier in Optical Imaging Techniques for Laparoscopic Surgery: An Industry Perspective.
Keywords: Biomedical engineering; Biophysics; Biomaterials; Lasers; Optical materials; Nanotechnology; Biomedical Engineering and Bioengineering; Biophysics; Biomaterials; Laser; Optical Materials; Nanotechnology